Experimental study on working characteristics of direct current plasma jet igniter. (28th June 2019) - Zhao, Zichen; He, Liming; Zhang, Hualei; Chen, Gaocheng; Zhao, BingBing; Liu, Xiong
Abstract: The flameout of the combustor at high altitude poses a great threat to the flight safety of the aircraft. The low temperature and pressure as well as thin air at high altitude make it difficult to successfully and reliably reignite. The direct current plasma jet, one of the promising plasma assisted ignition technologies, has been applied in the different engines. In this paper, the working characteristics (mainly including discharge characteristics and jet characteristics) of direct current plasma jet igniter is investigated experimentally by using electric signal, synchronously acquired arc movement pictures, and high speed schlieren pictures of plasma jet in both static flow field and cross flow field. The influence of the gas flow rate and cross flow velocity on the working characteristics of direct current plasma jet igniter is also studied. Results show that there are three stages (jet formation stage, jet expansion stage, and jet stability stage) form the breakdown of the igniter electrodes to the stable distribution of the jet in the combustion section. The operating voltage and fluctuation frequency rises significantly (from 92.55 V to153.11 V, and from 9.2 kHz to17.3 kHz), the influence area and penetration depth of plasma jet increased in cross flow environment with the increase of the gas flow rate. As the cross flow velocity increases, the three-dimensional fluctuation of arc movement is more obvious, the influence area and penetration depth of plasma jet decreases quickly. Both the discharge characteristics and jet characteristics affect the ignition capability of plasma jet igniter, and this study has certain guiding significance for the design of direct current plasma jet igniter.